Groundwater scarcity and management in the arid areas in East Africa - Kebede, S.; Taye, Meron Teferi (Elsevier, 2021)
Arid areas in East Africa are characterized by physical water scarcity. The physical water scarcity is further exacerbated by poor water quality (mainly salinity and fluoride) of mainly groundwater sources. Combined physical water scarcity and poor water quality makes the region a hydrogeologically difficult environment. Nevertheless, some viable high-yielding aquifers exist in East Africa. Difficult hydrogeology means that the best practices of reaching rural dwellers, towns, and urban centers require specialized financial, technical, and engineering approaches. The chapter describes the hydrogeology difficulty and the ongoing management strategies and its implications for the Water, Sanitation and Hygiene sector in East Africa arid regions.